이주의 재정효과에 관한 주류 경제학적 분석 비판 : 노동가치론의 관점에서 - 윤종희 (Journal of Global and Area Studies , 9(1), 2025)
유럽과 북미에서는 이주가 정부재정과 복지재정을 약화시킬 것이라는 대중적 불안 때문에 반(反)이주 정서가 확산되고 있다. 과연 이 같은 우려는 객관적 근거가 있을까? 이와 관련하 여 주류 경제학은 이주자와 내국인 각각의 순 재정기여도를 계산한 후, 두 집단을 비교함으 로써 이주의 재정효과를 분석한다. 개인의 순 재정기여도(Z)=국고에 납부한 금액(X )-공적 혜택의 화폐적 가치(Y). 그런데 이 같은 분석방법에서는 연구자의 주관에 따라 Y값이 다르게 계산된다. 이에 따 라 동일한 국가에서 동일한 자료를 가지고 계산해도 이주의 재정효과 (+)가 될 수도, (-)가 될 수도 있다. 하지만 대체로 이주자가 젊을수록, 숙련도가 높을수록, 체류기간이 짧을수록 이주의 재정효과가 높은 것으로 나타난다. 이에 따라 주류 경제학은 숙련도에 따라 이주자를 선별하고, 미숙련 노동자와 난민의 이주를 철저히 통제하고, 사회복지를 축소할 것을 제안한 다. 그러나 이 같은 정책은 이주의 재정효과를 높이지 못하고, 오히려 인종주의와 반(反)이주 정서를 부추긴다. 이 같은 문제는 주류 경제학의 이론적 결함에서 비롯된다. 분석의 객관성을 확보할 수 있 는 기준이 없고, 재정기여도 분석에서 법인을 배제할 뿐만 아니라 노동력의 (재)생산비용을 내국인에게 유리한 방향으로 계산한다. 결정적으로 이주가 거시경제에 미치는 영향도 충분히 고려하지 못한다. 이로 말미암아, 주류 경제학적 분석의 이주정책은 의도와 무관하게 호스트 국가의 거시경제와 정부재정에 부정적 영향을 끼친다. 본 연구는 주류 경제학적 접근에 대한 대안으로 고전파 경제학의 노동가치론을 제시한다. 노동가치론은 임금, 이윤, 지대가 각각 노동, 자본, 토지의 생산성에 따라 발생한다는 생산요 소설을 비판하고, 노동이 생산한 가치가 여러 계급으로 분배된다고 주장한다. 이에 따르면, 미숙련 이주자는 자신이 생산한 가치 중 상대적으로 적은 몫을 분배받기 때문에, 공적 재정 에 직접 기여하는 바가 작다. 그러나 그가 생산한 가치가 다른 계급의 소득으로 분배되어 간 접적으로 기여하는 부분이 크다. 그래서 본 연구는 이주자의 노동이 생산적으로 활용되는 한, 이주는 정부재정에 긍정적 효과를 가져올 것이라 주장한다. In Europe and North America, anti-migration sentiment is on the rise due to fears that migration will undermine the finances of the state and the welfare state. Thus the fiscal effects of migration are frequently utilized as an objective justification for developed nations today to determine the direction of their migration policies. It can be derived by calculating the net fiscal contribution of immigrants and natives and then comparing the two groups. “The net fiscal contribution(Z)= The amount paid into the national treasury(X)-The monetary value of public benefits(Y).” This methodology produces different values depending on the subjectivity of the researcher, so the fiscal impact of migration can be positive or negative even when using the same data for the same country. In general, however, the younger the migrant, the more skilled the migrant, and the shorter the stay, the higher the fiscal impact of migration. Mainstream economics therefore suggests screening migrants for skills, tightly controlling the migration of unskilled workers and refugees, and reducing social welfare. However, these policies do not increase the fiscal impact of migration, but rather fuel racism and anti-migrant sentiment. These problems stem from the theoretical flaws of mainstream economics. Not only does it exclude corporations from the analysis, but it also calculates the cost of producing a labor-power in a way that favors natives Crucially, it overlooks the macro-economic impacts of migration. As a result of these shortcomings, the migration policies proposed by mainstream economic analyses, despite their intentions, invariably yield detrimental consequences on the economy and public finances of host countries. As an alternative to the mainstream economic approach, this study proposes a labor theory of value. The labor theory of value criticizes the theory of factors of production, which states that wages, profits, and land are based on the productivity of labor, capital, and land, respectively, and argues that the value produced by labor is distributed among different classes. According to this labor theory of value, the unskilled migrant receives a relatively small share of the value he produces, so his direct contribution to public finances is small, but his indirect contribution is large because the value he produces is distributed as income to other classes. Thus, as long as the migrant’s labor is productively utilized, migration has a positive effect on government finances, regardless of his net fiscal contribution. KCI Citation Count: 0